Everyday Lives in Occupied Poland. Some Ideas for a (Slightly) Different View - Kochanowski, Jerzy (Acta Poloniae Historica, 2022)
This article (or rather this essay) demonstrates several possibilities for a slightly different perspective on not so much everyday life during the occupation but on everyday lives. Only within the framework of the German occupation, which from the summer of 1941 covered almost the entire pre-war territory of Poland, the range of differences, both between administrative units (e.g., the General Government, the Wartheland or the Eastern Borderlands) as well as within them, between city and countryside, between individual social, professional, ethnic and age groups, was vast. The occupation was not a static and homogeneous phenomenon but a diverse and dynamic one, full of complex interactions. This text, based variously on the subject literature, published and archival sources (Polish and German), clandestine and official press, focuses on the following phenomena: the situation of Polish officials working for the occupation administration, mobility (both spatial and social – horizontal and vertical), relations between the city and the countryside, the breakdown of social norms, the wartime economy (with a greater than usually considered subjectivity of Polish actors) or the process of ‘taming’ the occupation (including terror), both materially and psychologically. The text may be treated as encouragement and invitation to interdisciplinary, methodologically innovative, cross-sectional research on Polish society during the Second World War.